2022
DOI: 10.1002/mma.8448
|View full text |Cite
|
Sign up to set email alerts
|

Solvability of mixed problems for the wave equation with reflection of the argument

Abstract: The paper considers mixed problems for the wave equation with reflection of the argument, with a complex-valued variable coefficient. The existence and uniqueness of solution of the studied problems is established by the method of separation of variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…This proves the uniform convergence of the series u xxxx (x, t) in the open domain Ω. Thus, we have shown that series (17), (18) satisfy equation (4).…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…This proves the uniform convergence of the series u xxxx (x, t) in the open domain Ω. Thus, we have shown that series (17), (18) satisfy equation (4).…”
Section: Resultssupporting
confidence: 69%
“…The existence and uniqueness of the solution of mixed problems for the heat equation with a complex-valued coefficient was established in [3]. The solvability of mixed problems for a perturbed wave equation with involution and with a variable complex-valued coefficient was studied in [4,5]. The solvability of inverse problems for the perturbed heat equation with involution and with a variable complex-valued coefficient was considered in [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly true for numerical approaches that deal with this category of problems. Recent research has focused on inverse problems involving perturbations of the involution type, as seen in the literature [8,9,[14][15][16].…”
Section: Direct Problem For Time-fractional Heat Equation With Involu...mentioning
confidence: 99%